Community‐acquired Acute Kidney Injury Among Children Seen in the Pediatric Emergency Department. (1st May 2018) - Bernardo, Erika O.; Cruz, Andrea T.; Buffone, Gregory J.; Devaraj, Sridevi; Loftis, Laura L.; Arikan, Ayse Akcan
Abstract: Objectives: Acute kidney injury (AKI) is a significant risk factor for morbidity and mortality in children. Little is known about community‐acquired AKI (CA‐AKI) in the pediatric emergency department (PED). Early recognition of AKI allows for nephroprotective measures. The goal of this investigation was to determine the incidence of CA‐AKI and the frequency of clinician identified CA‐AKI to better inform future nephroprotective interventions. Methods: This was a retrospective cross‐sectional study in the PED of a children's hospital. Children 1 month to 18 years of age seen in the PED from January 1 to December 31, 2015, and in whom at least one creatinine level was obtained were included. Patients with chronic kidney disease or end‐stage renal disease or who died in the PED were excluded. Patients had CA‐AKI based on modified Kidney Disease‐Improving Global Outcomes criteria using the creatinine obtained in the PED compared to age‐specific norms. Patients were considered identified if the PED clinician diagnosed AKI. The primary outcome was the incidence of CA‐AKI. Secondary outcomes included frequency of AKI identification, nephrotoxic medication use, hospital length of stay, renal replacement therapy, and death. Fisher exact test or Pearson's chi‐square test was used to calculate odds ratio (OR) with 95% confidence intervals (CIs); multivariable analyses were performed using logistic regression. Results: In 2015 there were 119, 151 PED visits; 15, 486 met inclusion criteria. CA‐AKI was present in 239 of 15, 486 (1.5%) encounters. AKI was identified by PED clinicians in 46 of 239 (19%) of encounters and by the inpatient team in 123 of 199 (62%) of the encounters admitted. AKI was never recognized by a PED or inpatient clinician in 74 of 199 (37%) encounters. Encounters with AKI correctly diagnosed were older (13 years old vs. 10 years old, p = 0.0114), had more severe (stage 2 or 3) AKI (OR = 5.5, 95% CI = 2.6–11.8), and were more likely to be admitted (OR = 10.3, 95% CI = 1.38–77.4) than encounters with missed AKI. Conclusions: CA‐AKI remains an underrecognized entity in the PED. Better tools for early recognition of AKI in the busy PED environment are needed.